Photodynamic therapy and tumor-treating fields therapy for newly diagnosed glioblastoma - Fukami, Shinjiro; Nagai, Kenta; Onodera, Sho; Saito, Yuki; Akimoto, Jiro; Kohno, Michihiro (Frontiers in Oncology, 2025)
Introduction and purposeVarious treatment methods, including photodynamic therapy (PDT), are used for glioblastoma (GBM), which is an intractable tumor. Our therapeutic strategy for glioblastoma has been based on resection (if possible), and PDT. On the other hand, after tumor-treating fields therapy (TTF) became available, we have actively recommended it to our patients who are eligible for it. In this report, we describe the clinical characteristics and disease course of glioblastoma patients treated by PDT + TTF at our hospital.MethodsA total of 14 patients with newly diagnosed glioblastoma, who underwent PDT + TTF from the time of insurance coverage of TTF were analyzed. The median age of the patients was 48 years. There were 10 men and 4 women, with a high prevalence of younger men.ResultsThe average duration of TTF was 8.9 (1–19) months, and the main reasons for its discontinuation were recurrence of the tumor and scalp problems. The median progression-free survival of the 14 patients who underwent PDT + TTF was 13.4 months, which tended to be longer than that of the 30 patients who underwent PDT without TTF (11 months). Of the 10 patients who relapsed, 2 had local recurrence and 8 had distant or disseminated recurrence. Two patients with local recurrence underwent repeat resection together with PDT. To date, the prognosis for patient survival of PDT + TTF appears favorable, with 6 patients surviving for more than 2 years.ConclusionPDT + TTF treatment for newly diagnosed glioblastoma can be performed without any major adverse events, although there are some problems with the continuation of TTF, such as scalp problems and its high cost. More patients who underwent PDT + TTF relapsed with distant and/or disseminated recurrence than local recurrence, suggesting that this treatment strategy targets local recurrence. Our results demonstrate that combination therapy for newly diagnosed glioblastoma with PDT + TTF may prolong the time to recurrence and improve survival outcomes of patients, although the data in this study are preliminary.